Oxygen permeability properties of nanocellulose reinforced biopolymer nanocomposites - Ilyas R.A.; Azmi A.; Nurazzi N.M.; Atiqah A.; Atikah M.S.N.; Ibrahim R.; Norrrahim M.N.F.; Asyraf M.R.M.; Sharma S.; Punia S.; Syafri E.; Sari N.H.; et al. (Elsevier Ltd, 2023)
Biodegradable polymers; Biofilms; Biomolecules; Nanocellulose; Nanocomposite films; Nanocomposites; Oxygen; Oxygen permeable membranes; Packaging; Packaging materials; Reinforcement; Sustainable development; Tensile strength; Water vapor; Dry powders; Nano-cellulose; Oxygen permeability; Oxygen vapors; Permeability properties; Plastics waste; Powder products; Property; Shelf life; Water vapour; Biopolymers